PENGARUH FAKTOR FINANSIAL DAN NON-FINANSIAL TERHADAP KEPUASAN KERJA DOSEN P-MKDU INSTITUT PERTANIAN BOGOR - Barus, Irma Rasita Gloria; Sulistiarti, Dwiningsih; Soedewo, Tatie (Ilmiah Manajemen Bisnis, 2011)
ABSTRACTÃÂ Lecturers are the assests of a higher educational institution, and they are professional educators and scientists whose main main tasks are to transform, develop and disseminate science and technology, and arts. In order to carry out their duties, the lectuers must be satisfied in carrying out their work. Determinants of job satisfaction include financial variables (measured in monetary measurement) and non-financial variables (measured in non-monetary measurement). ÃÂ The research results from the survey conducted on the lecturers of P-MKDU show that financial and non-financial variables can explain the variations in job satisfaction i.e. as much as 47 %. The influence of financial and non-financial variables on job satisfaction is shown by the regression equation of Y = 6,367 + 0,532 X1 + 0,044 X2.. The influence of financial variables (X1) on job satisfaction (X2) is as much as 0.532 whereas the influence of non-financial variables (X2) on job satisfaction is as much as 0.044. From these results, it can be seen that financial variables have more influence on job satisfaction than the non-financial variables.ÃÂ ÃÂ ÃÂ ÃÂ Key words: Job satisfaction, financial variables, non-financial variables